2021
DOI: 10.3390/jmmp5030081
|View full text |Cite
|
Sign up to set email alerts
|

New Abrasive Coatings: Abraded Volume Measurements in Ceramic Ball Production

Abstract: Technological progress in hybrid bearings developed high wear and abrasion resistant materials for rolling elements. The manufacturing process of bearing balls presents new challenges, as nowadays, it requires time-consuming and costly processes. In this frame, the bearing manufacturing industry is demanding improvements in materials, geometry, and processes. This work aims to investigate new abrasive coatings for grinding wheels for Si3N4 ball manufacturing. Tribological pin on disk tests are performed on sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In [26], the test preload was lower (1 N vs. 5 N) and this wear effect on the disks was less evident. In [26], the average dimension of the particles was less than the half of the present ones.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…In [26], the test preload was lower (1 N vs. 5 N) and this wear effect on the disks was less evident. In [26], the average dimension of the particles was less than the half of the present ones.…”
Section: Resultsmentioning
confidence: 92%
“…The results of abrasion on the processed balls are reported in Figure 8 and Figure 9. In Figure 8, the ball volume loss Vb (mm 3 ), the wear rate u (μm/h), and the wear coefficient k are calculated as described in [26] and then reported, while in Figure 9, the roughness parameters measured on the abrasion surface of the balls are reported. It can be observed that, with increasing linear speed, the quality of abraded balls worsens when processed with Ni-Dia surfaces, while in the case of Ti-Dia surfaces, the effect of linear speed seems to improve the quality of the abraded surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations